THE FRIENDSHIP VALUES BETWEEN THE MAIN CHARACTERS AS REFLECTED IN KATHERINE PATERSON’S BRIDGE TO TERABITHIA: A PSYCHOLOGICAL STUDY - Agus Mustajib (Fakultas Keguruan dan Ilmu Pendidikan, 2020)
This research entitled